PENGARUH MODEL PEMBELAJARAN INQUIRI DENGAN TEKNIK PICTORIAL RIDDLE TERHADAP KEAKTIFAN DAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI TANJUNG RAJA - Winda Novlina Sinaga; M. Djahir Basir; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The formulation of the problem in this research is how is the influence of inquiri model of learning with pictorial riddle technique to the activity and motivation of student learning on economic subjects of SMA Negeri 2 Tanjung Raja. The purpose of this research is to know the influence and how the influence of inquiri model of learning with pictorial riddle technique to the liveliness and motivation of student learning on economic subjects of SMA 2 Tanjung Raja. The population in this study is the number of all students class X IPS, amounting to 44 students consisting of two classes of class X IPS 1 and X IPS 2 in the academic year 2013/2014. Sample selection was taken by using purposive sampling technique and obtained X IPS 2 as a sample of research which amounted to 23 students. This research uses Pre-Experimental Design research method of one-shot case study. Data collection techniques in this study using Observation and Questionnaire. Observation is used to measure activity while questionnaire is used to measure motivation through observation sheet and questionnaire. From the results of hypothesis testing active t_ (count) = 54.32>t_tabel = 0.686 and motivation hypothesis t_hitung>t_table = 0.686 This shows that there is influence of inquiri model of learning with pictorial riddle technique to the liveliness and motivation of student learning on economic subjects SMA Negeri 2 Tanjung Raja and the process of applying the model proved to generate activeness with very active criteria and motivation with very high criteria.